Clinicopathological Characteristics of Primary Appendiceal Mucinous Neoplasm and Recurrence After Radical Resection - Wang, Zaibiao; Yin, Manman; Shao, Jiayun; Yin, Zhipeng; Peng, Jie; Lu, Zhengmao (Frontiers in Surgery, 2022)
Objective Appendiceal mucinous neoplasm (AMN) is a rare obstructive dilatation of the appendix caused by an intraluminal accumulation of mucoid material, showing an insidious onset and few specific clinical manifestations. The purpose of the study is to analyze clinicopathological characteristics of primary AMN and recurrence after radical resection. Methods A total of 50 patients were included in the retrospective cohort study of AMN. Patient data, such as demographics, tumor characteristics, surgical management, preoperative serum carcinoembryonic antigen (CEA), and carcinoembryonic antigen 19-9 (CA19-9) levels, were collected. All patients were followed-up with interval CT scans until the end of December 2021, with overall survival (OS) and progression-free survival (PFS) being calculated. Results All patients were confirmed as AMN by pathological diagnosis after surgery, including 28 cases (56.00%) of low-grade AMN (LAMN) and 22 cases (44.00%) of non-LAMN. Among 50 patients with AMN, there were 12 cases (24.00%) complicated with pseudomyxoma peritonei (PMP). Higher proportions of patients with pTis, pT3, pT4a, ruptured at presentation, and PMP were found in patients with non-LAMN patients than LAMN (p < 0.05). There was a remarkable difference about preoperative serum CA19-9 levels between patients with LAMN and non-LAMN (p = 0.044). Patients complicated with PMP had a higher proportion of patients with ruptured at presentation than those who were not (p < 0.001). The patients with PMP had increased tumor size compared with those without PMP (p = 0.031). Remarkable differences were observed in terms of preoperative serum CA19-9 (p = 0.009) levels between patients with PMP and without PMP. We performed a multivariate analysis of the presence or absence of PMP and found that ruptured at presentation was found to be a risk factor for PMP in patients with AMN (p = 0.003). The PFS in the patients with PMP and those without was 33.33% (4/12) and 2.63% (1/38), showing a significant difference (P = 0.002). Conclusion The study demonstrates that ruptured at presentation and PMP may influence the prognosis and survival of patients with AMN.